AN ANALYSIS ON THE FACTORS WHICH INFLUENCE FINANCIAL STATEMENT QUALITY OF THE LANGKAT DISTRICT ADMINISTRATION WITH MANAGERIAL COMMITMENT AS MODERATING VARIABLE - Yusnita, Erna Tengku (Asosiasi Dosen Akuntansi Indonesia, 2018)
The objective of the research was to analyze the influence of the implementation of Government Accounting Standard, Quality of Human Resources, Government Internal Control System, the Use of Information Technology, and Managerial Commitment as moderating variable on the Quality of Financial Statement in Langkat District Administration. The research used quantitative causal comparative method. The population was the Financial Administrative personnel involved in managing finance at 54 SKPDs in Langkat District Administration. The samples were taken by using census method (total sampling technique) The data were analyzed by using Partial Least Square (PLS) 3.0. The result of the research showed that Government Accounting Standard, Quality of Human Resources, Government Internal Control System, the Use of Information Technology, and Managerial Commitment had the influence on the quality of financial statement of Langkat District Administration. Managerial Commitment could moderate the correlation of Government Accounting Standard with the Quality of Financial Statement. Managerial Commitment could moderate the correlation of Quality of Human Resources with the Quality of Financial Statement. Managerial Commitment could not moderate the correlation of Government Internal Control System with the Quality of Financial Statement. Managerial Commitment could not moderate the correlation the Use of Information Technology with the Quality of Financial Statement.